(untitled) (Bangladesh Journal of Microbiology, 2019)
Infections due to Gram-negative bacteria are common affairs in cancer patients during aggressive therapy. The present study characterizedmulti-drug resistant bacteria (MDR) isolated from cancer aspirates collected from patients admitted to the National Cancer Hospital in Dhaka, Bangladesh. A total of 210 aspirate samples were collected from cancer patients. Out of 210 samples Acinetobacter spp.led the list of isolates (8.89%, n=45). Of these species, 50% exhibited resistance to Amoxycillin and Nitrofurantoin, each, 25% exhibited resistant to Cefotaxime, Azithromycin, Ciprofloxacin, Clindamycin, and Sulfamethoxazole. A total of 33.33% of the Bordetella spp.which accounted 6.67%of the total isolates exhibited resistance to Cefotaxime. All oftheLegionellapneumophila,comprising 4.4%of the isolated species, wereresistant to Cefotaxime, Azithromycin, and Clindamycin.In contrast, 50% were resistant to Cefotaxime, Azithromycin, and Ceftriaxone. Of the Escherichia coli(4.4%, n=45) isolated,50% exhibited resistance to Cefotaxime, Clindamycin, Ceftriaxone, Amoxycillinand Sulfamethoxazole.The only isolate of Klebsiella sp. was demonstrated to be an ESBL producer. The isolation of multidrug resistant bacteria from cancer patients is of particular concern in Bangladesh where cancer and drug resistance are both common phenomena but treatment facilities are poor. To our knowledge this is the first report of the isolation of drug resistant bacteria from cancer patients from Dhaka city. Bangladesh J Microbiol, Volume 35 Number 1 June 2018, pp 61-66